2013
DOI: 10.1136/annrheumdis-2013-203243
|View full text |Cite
|
Sign up to set email alerts
|

A two-step treatment strategy trial in patients with early arthritis aimed at achieving remission: the IMPROVED study

Abstract: Initial MTX and prednisone resulted in early remission in 61% of patients with early (rheumatoid) arthritis. Of those, 68% were in remission and 32% were in drug-free remission after 1 year. In patients not in early remission, earlier introduction of ADA resulted in more remission at year 1 than first treating with disease-modifying antirheumatic drug combination therapy plus prednisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 27 publications
4
70
0
13
Order By: Relevance
“…Also, in the IMPROVED study, patients who were treated for flares based on DAS28 criteria had similar efficacy outcomes to those who were treated based on nonprotocol‐endorsed criteria, demonstrating that DAS28‐based criteria to detect flares that matter for outcomes are limited 9.…”
Section: Discussionmentioning
confidence: 94%
“…Also, in the IMPROVED study, patients who were treated for flares based on DAS28 criteria had similar efficacy outcomes to those who were treated based on nonprotocol‐endorsed criteria, demonstrating that DAS28‐based criteria to detect flares that matter for outcomes are limited 9.…”
Section: Discussionmentioning
confidence: 94%
“…Our analysis showed that the effect of a TNF inhibitor plus methotrexate was significantly superior to combination DMARD treatment during the first 6 months, but this difference almost disappeared after 12 months, and especially after 18/24 months (no outcomes differed). Furthermore, in 3 studies using an initial course of steroids (3,4,14,15), there was no difference between the 2 treatment principles at any time (Figures 2-5 and Supplementary Figures 1-3, available in the online version of this article at http://onlinelibrary.wiley. com/doi/10.1002/acr.22618/abstract).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning outcomes, only 1 study presented ESRs (14), 1 study presented CRP levels (11), and 3 studies presented joint swelling scores (10,14,16). Consequently, these outcomes, which we defined in the protocol, were not summarized in the present analysis.…”
mentioning
confidence: 99%
“…In this randomised study with a blinded outcome assessment (disease activity score and radiographic damage score), the GC arm showed a higher rate of improvement at week 28 than with SSZ alone (72 versus [58] and COBRA-light [59]) helped build on the idea that there was a ''window of opportunity'' in early RA and that tight control the Aging Clin Exp Res (2016) 28: 1-16 5 inflammation or ''treating-to-target'' (i.e. remission or minimal disease activity) resulted in better long-term outcomes.…”
Section: Gc Therapeutic Strategies In Ramentioning
confidence: 99%